(untitled) (Agroindustrial Science, 2022)
Over the years, the poultry industry has used various types of promoters to improve production; however, the current trend is to eliminate the growth promoters that cause resistance in humans, for example, the antibiotics in the European Union, there is a need to look for natural alternatives that are beneficial for the body and do not have a negative impact on the human health. The objective of the present study was to evaluate the productive parameters, in pullets from one to 16 weeks of age, when using a growth promoter in the feed, made from soursop leaf ferment, as well as to determine its influence on production costs. The study population consisted of 200 Hy Line Brown pullets. A Completely Randomized Design (DCA), a treatment and a control, were used. Production parameters were recorded: weekly weight, feed consumption and feed conversion, in addition to recording production costs. The results showed that between the treatment and the control there was no significant difference between the productive parameters. However, the production cost favored the growth promoter treatment (S/16.87) compared to the control (S/17.47), making its use possible in the natural feeding of birds.